مصارف الأوقاف في مؤسسات العمل الخيري المعاصر ودور الدولة في تنظيمها : دراسة فقهية تطبيقية على دولة الكويت - عبيد،آلاء عادل جاسم (Institute of Islamic Banking and Finance, International Islamic University Malaysia, 2016)
This study discusses the principles of waqf and its application in respect of the distribution channels of waqf in contemporary charitable work establishments and the role of the state in regulating them according to the principles of Sharī'ah with particular reference to the State of Kuwait. This study aims at defining the distribution channels of waqf, their types, and ways in regulating them. The purpose of the study is to highlight the most important criteria upon which the distribution channels of waqf are determined and to discuss the extent of which the Sharī'ah will recognise the intention of the waqf donors (the wāqifs) in establishing the waqf, within the parameters of maqāṣid al-Sharī'ah and 'urf that are acceptable. It also discusses some important practical problems that are faced by the distribution channels of waqf. In doing so, it shall apply the principles of Sharī'ah in determining the correct approach towards that. It also discusses the correct practices of the distribution channels of waqf to be implemented based on the opinions of scholars and best practices for the purpose of completed the positive aspects of waqf distribution channels and to address the shortcomings of the practice. from the Sharī'ah perspective. In conclusion, it will also explain some of the experience of the Kuwaiti waqf endeavours regarding the distribution channels of waqf. This study is based on qualitative research methodology and applies the following empirical approaches: the inductive approach, the analytical approach, the deductive approach, field study approach, and the approach of critique, contrast, and opting. This study demonstrates the importance of directing the distribution channels of waqf towards serving basic needs of the society based on valid priorities and the maqāṣid al-Sharī'ah. The researcher concluded her study with numerous recommendations which may serve for the betterment of the distribution channels of waqf in contemporary charitable work.